Emotional and affective geographies of sustainable community leadership: A visceral approach. Issue 106 (November 2019) - Duffy, Michelle; Gallagher, Michael; Waitt, Gordon
Highlights: Significance of affective and visceral relations in choices made by sustainability leaders. Walking-as-method is a strategic means to access these relations and their significance. An ethics of hope considers capacity and vulnerability as significant to emergence of leaders. Abstract: In this paper, we aim to better understand what mobilises people into being and becoming named as leaders in sustainability in the places where they live. Our premise is that action for sustainability originates with passionate individuals who lead action at the local level. We present our analysis of a walking sensory ethnography conducted in 2012 undertaken as part of exploratory research on adaptation to climate change in the coastal town of Dunbar, Scotland. We sought to understand the complex, embodied and sensorial ways in which places, and our experiences of connection to places, are constituted. The starting point for our discussion is the recognition of the intricate, deeply entangled relations between the human and nonhuman world that have historically been obscured by western understandings of a pristine nature set apart from the world of human culture. Building on literature under the umbrella of "Anthropocene feminisms", we suggest that a visceral approach as conceptualised in the work of Hayes-Conroy and Hayes-Conroy (2008) and Hayes-Conroy and Martin (2010) offers embodied knowledge as a radically relational view of the world that allows an entry into the ways in which the micro-scale of the body intersects with the global scale of political praxis. Our detailed discussion of one of our research participants provides an example as to how this individual came to feel connected through a shared sense of consciousness with the human and non-human. In this exploration, we found possibilities in thinking beyond the otherwise paralysing narratives of anthropogenic climate change. Our argument is that this focus brings to the fore the transformative capacity of viscera, emotional and affective responses to anthropogenic climate change, and that these are integral to hope, albeit this is a hope that needs to consider capacity and vulnerability in new ways.